Relaxin: Review of Biology and Potential Role in Treating Heart Failure - Teichman, Sam L. (Current Science Inc., 2010)
Relaxin is a naturally occurring human peptide initially identified as a reproductive hormone. More recently, relaxin has been shown to play a key role in the maternal hemodynamic and renal adjustments that accommodate pregnancy. An understanding of these physiologic effects has led to the evaluation of relaxin as a pharmacologic agent for the treatment of patients with acute heart failure. Preliminary results have been encouraging. In addition, the other known biologic properties of relaxin, including anti-inflammatory effects, extracellular matrix remodeling effects, and angiogenic and anti-ischemic effects, all may play a role in potential benefits of relaxin therapy. Ongoing, large-scale clinical testing will provide additional insights into the potential role of relaxin in the treatment of heart failure.